RICE (ORYZA SATIVA L.) INPARI 42 VARIETY GROWTH AND PRODUCTION IN RESPONSE TO BOKASHI AND PHONSKA NPK FERTILIZER - Musadia Afa; Djunarlin Tojang; Fitrianti Handayani (ITScience (Information Technology and Science), 2023)
This study aims to investigate the optimum dosage of Bokashi and Phonska NPK fertilizer on the growth and production of the Inpari 42 rice variety. This investigation was conducted at the agricultural location of Ulu Mowewe Village, Mowewe District, East Kolaka Regency. The experiment used was the Split Plot Design (RPT). The factorial pattern consists of two treatment factors, namely the Bokashi (B) treatment factor with three levels, namely: B1 = 1.2 kg/plot, B2 = 2.4 kg/plot, and B3 = 4.8 kg/plot, and the treatment factor Phonska NPK, which consists of three levels, namely N1 = 0.18 kg/plot, N2 = 0.36 kg/plot, and N1 = 0.54 kg/plot. Parameters observed in the study were: plant height, number of tillers, number of leaves, leaf length, leaf width, panicle length, number of panicles or clumps, number of grain or panicles, number of filled grain or panicles, the weight of 1000 grain grains, dry milled grain yield (GKG) per plot, Milled Dry Unhulled grain yield (GKG) per conversion. The data were processed using variance (ANOVA) and followed by the Least Significant Difference Test (LSD). Based on the results of the study, it can be concluded that the combined dose of Bokashi and Phonska NPK fertilizer significantly affected plant height (cm), the number of tillers, the number of leaves (strands), leaf length (cm), leaf width (cm), panicle length (cm), number/panicle, total grain/panicle, total grain/panicle, and yield of dry milled grain (GKG)/slot (kg), the yield of dry milled unhulled grain (GKG)/conversion (tons) The dose treatment of Bokashi and Phonska NPK showed that the optimum combination dose of Bokashi and Phonska NPK for the growth and yield of Inpari 42 rice was B3N2 (4.8 kg and 0.3 kg/plot).